Knowledge, attitudes and practices relevant to malaria elimination amongst resettled populations in a post-conflict district of northern Sri Lanka. - Kirkby, K; Galappaththy, G; Kurinczuk, J; Rajapakse, S; Fernando, S (2013)
BACKGROUND: Malaria-related knowledge, preventative methods and treatment-seeking behaviours were investigated in a post-conflict district of Sri Lanka in order to guide the development of components of malaria interventions and to support future programme evaluation. METHODS: A structured questionnaire was used to collect data from a random sample of 300 households in four Divisional Secretariat Divisions (DSD) of the district where internally displaced populations were being resettled after a 30-year civil war. RESULTS: The surveyed community had a good overall level of knowledge of malaria. There was high bednet ownership (94.0%), although only 48.0% of households in the study had long-lasting insecticide-treated nets (LLIN). Most respondents reported rapid treatment-seeking behaviour (71.0%) and easy access to malaria diagnostic facilities (67.0%). The Tamil population living in Manthai West and Madhu DSDs who were displaced to refugee camps had better malaria-related knowledge and practices, probably due to the malaria control activities focused on these camps by the government. CONCLUSIONS: Although knowledge and practices regarding malaria amongst resettled populations in Mannar District were high, continued malaria surveillance, case management, vector control including distribution of LLINs, education and information campaigns are important not only amongst the communities affected by the conflict but the entire district.